Hematological Reference Values for Healthy Adults in Togo. (7th November 2010) - Kueviakoe, Irenee Messanh; Segbena, Akuete Yvon; Jouault, Helene; Vovor, Ahoefa; Imbert, Michele
Abstract : The hematological reference values are very important for diagnostic orientation and treatment decision. The aim of this study was to establish hematological reference values for healthy adults in Togo. A total of 2571 voluntary blood donors participated to this study. Only 1349 subjects negative for HIV, HBV, HCV, malaria, and without hemoglobin abnormalities in electrophoresis and hypochromia on blood smear, were definitively retained for the study. Median hemoglobin level was higher in males than females (15.1 g/dL versus 13.0 g/dL, p = 0.000 ). Median total WBC (4.2 × 10 9 /L) and absolute neutrophil counts (1.6 × 10 9 /L) were similar by gender. The median lymphocyte counts in males and females were, respectively, 2.1 × 10 9 /L and 2.2 × 10 9 /L (p = 0.11 ). The median platelet count was lower in males than females (236 × 10 9 /L versus 247 × 10 9 /L, p = 0.004 ). Our median values for RBC parameters differ from those of African countries probably because of our inclusion criteria which eliminate most cases with iron deficiency and/or thalassemia.